Supporting mobile mixed-reality experiences - Flintham, Martin (2009)
Mobile mixed-reality experiences mix physical and digital spaces, enabling participants to simultaneously inhabit a shared environment online and on the streets. These experiences take the form of games, educational applications and new forms of performance and art, and engender new opportunities for interaction, collaboration and play. As mobile mixed-reality experiences move out of the laboratory and into more public settings they raise new challenges concerning how to support these experiences in the wild.